Determining Metal Ion Complexation Kinetics with Fluorescent Ligands by Using Fluorescence Correlation Spectroscopy. Issue 16 (10th July 2019) - Sharma, Arjun; Sarkar, Aranyak; Goswami, Dibakar; Bhattacharyya, Arunasis; Enderlein, Jörg; Kumbhakar, Manoj
Abstract: Fluorescence correlation spectroscopy (FCS) has been extensively used to measure equilibrium binding constants ( K ) or association and dissociation rates in many reversible chemical reactions across chemistry and biology. For the majority of investigated reactions, the binding constant was on the order of ∼100 M −1, with dissociation constants faster or equal to 10 3 s −1, which ensured that enough association/dissociation events occur during the typical diffusion‐determined transition time of molecules through the FCS detection volume. However, complexation reactions involving metal ions and chelating ligands exhibit equilibrium constants exceeding 10 4 M −1 . In the present paper, we explore the applicability of FCS for measuring reaction rates of such complexation reactions, and apply it to binding of iron, europium and uranyl ions to a fluorescent chelating ligand, calcein. For this purpose, we exploit the fact that the ligand fluorescence becomes strongly quenched after binding a metal ion, which results in strong intensity fluctuations that lead to a partial correlation decay in FCS. We also present measurements for the strongly radioactive ions of 241 Am 3+, where the extreme sensitivity of FCS allows us to work with sample concentrations and volumes that exhibit close to negligible radioactivity levels. A general discussion of the applicability of FCS to the investigation of metal‐ligand binding reactions concludes our paper. Abstract : Fluorescence correlation spectroscopy and fluorescence time trace analysis were employed to explore binding constants and kinetics involving metal ions with fluorescent chelating ligands forming thermodynamically stable complexes.